Analysis of Temperature Distribution and Rate of Heat Transfer on Cooling System (Simulation) Using Porous Media - Su'udy, Ahmad Hamim; Siswanto, Eko; Soenoko, Rudy (Rekayasa Mesin, 2018)
Science and technology continue to innovate to overcome the problem of cooling systems that often arise from heat generated by the engine and how to improve engine cooling function. The porous media system provides a solution for heat transfer with porous media capable of enhancing heat transfer, as well as the effect of natural convection with porosity variation. The high porosity increases the Prandtl value proportional to the Nusselt value, causing the flow value to increase as well. The study of heat transfer with porous media can be applied to engine cooling system using simulation aid, with porosity 10%, 15%, 20%, 25%, 30%. Where the results obtained porosity affect the temperature distribution where the greater the value of porosity the greater the temperature distribution occurs and the greater the porosity then the value Thermal conductivity is smaller, Small thermal conductivity causes the rate of heat transfer is also small.